Peppering versus Single Injection Technique in Tennis Elbow - A Prospective Comparative Study - Prakash YR; Dhanda A; Yallapur KL; Inamdar SS; Darshan GT; Ramakrishna M (Malaysian Orthopaedic Journal, 2022)
INTRODUCTION: Lateral epicondylitis is a common condition causing severe incapacitating pain. Several methods of treatment have been approached for its management. In our study we aim to compare the results of injecting steroid and lignocaine mixture via single injection and peppered injection technique and analyse the outcome in each category. MATERIALS AND METHODS: A prospective randomised study comprising of 25 patients in each group (single vs peppered group) were included in the study after satisfying inclusion and exclusion criteria. Outcome of the treatment was measured in the form of Patient Related Tennis Elbow Evaluation (PRTEE) Questionnaire, Visual analogue score (VAS) and tenderness grading at two weeks, six weeks and six months after injection. RESULTS: Results of our study showed that the mean PRTEE score was 22.36, 18.40 and 14.16 at 2 weeks, 6 weeks and 6 months following peppered injection as compared to 28.96, 21.84 and 25.32 in the single injection group (p value <0.05). VAS score at 2 weeks, 6 weeks and 6 months after the peppered injection was found to be 2.72, 1.72 and 1.36 and in the single injection group was 2.96, 1.92 and 2.72 at 2weeks, 6 weeks and 6 months, respectively (p value <0.05). On comparison of the 2 groups, there was a significant reduction of VAS scores at 6 months post-injection (p value <0.05) and PRTEE score at 6 weeks, 6 months in peppered injection group. CONCLUSION: The effects of peppered injection technique is seen to be advantageous over the single injection technique in the management of chronic lateral epicondylitis.